(3TQM GdUdhGJ GdOQOjQjI Ydi NjQ GdHQjIs - (3CMeO Hf eMeO GdUGhj GdeGdcjs ((3MSjf GdLSQ Hf eMeO GdLSQ GdMfai GdWQGHdSi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ChLH YdjfG GdUdGI hGdSdGe Ydi SjO GdCfGe hHYO ajbhd CMeO Hf eMeO GdUGhi GdeGdci bO CeQfi TjN GdhbJ hGdWQjbI SjOi GdTjN UGdM GdSHGYi Cf CTQM UdhGJ CHh GdHQcGJ CMeO Hf eMeO GdOQOjQ GdYOhi s
(3BNQgG (B:s
(3hbhdg hYefG Ci ELYd GdUdGI TGedI dfG HWQjb GdJHY dNjQJc ef Ndbc hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJUha hGdBOGH GdTQYjIs